From char to harvest: unveiling biochar’s impact on soil health and crop productivity - Suriya, K; Prabhaharan, J; Sheeba, S; Mini , M L; Sampath , T K; Uma , R S; Krishnakumar, S; Murugaragavan , R (Plant Science Today, 2025)
Biochar is a stable carbon-rich by-product through pyrolysis of biomass under limited oxygen conditions. It has emerged as a sustainable strategy for enhancing soil health and agricultural productivity. This review synthesized recent research both on the positive and negative impacts of biochar application across different soil types and cropping systems, with particular focus on its relevance to India’s agrarian economy. Biochar has been shown to improve soil physical properties such as bulk density, porosity, water retention and aggregate stability. Chemically, it enhances nutrient retention by increasing cation exchange capacity, soil pH and organic carbon content. Biologically, biochar supported microbial abundance, enzyme activities and biomass carbon, especially in nutrient-deficient or acidic soils. Consequently, numerous studies reported increased crop yields, particularly in degraded or low-fertility soils. However, adverse outcomes were also observed including nutrient immobilization, increased salinity and microbial shifts that suppress plant growth often linked to excessive dosages, incompatible soil types or unsuitable biochar characteristics. Additionally, biochar’s role in long-term carbon sequestration and greenhouse gas mitigation including reductions in N₂O and CH₄ emissions was explored. While findings highlighted biochar’s multifaceted potential, variability in its performance underscored the need for site specific applications and standardized protocols. The review concluded by identifying critical research gaps and providing direction for optimizing biochar use in sustainable agriculture and climate-resilient farming systems.